ANALYSIS OF THE IMPACT OF FOREST FIRES ON THE COMMUNITY OF MUARA MERANG VILLAGE, BAYUNG LENCIR DISTRICT, MUSI BANYUASIN REGENCYSOUTH SUMATERA PROVINCE - Tedrik Apriansyah; Syafrul Yunardi; Ir. Lulu Yuningsih, S.Hut, M.Si, IPU (Sylva Jurnal Ilmu-ilmu Kehutanan, 2025)
Based on data from the number of hotspots in South Sumatra Province in 2020, Musi Banyuasin (Muba) Regency has the highest hotspots compared to other regencies, namely 623 points. One of the areas experiencing forest fires in Muba Regency is Muara Merang Village. The Muba Regency Government admitted that around 50% of the 719,976 ha of forest area in Muba was damaged.Based on these conditions, the problem arises of how much of the community's cultivated land was burned and what impact the fire had on community income and community activities, so the aim of the study was to determine the impact of forest fires on the income and activities of the Muara Merang Village community.This research method uses a survey research method with a qualitative and quantitative approach. Data collection uses triangulation methods through observation, interviews and documentation. The population in this study is Muara Merang Village with samples consisting of Bakung Hamlet, Tebing Harapan Hamlet and Pancoran Hamlet. Data analysis uses descriptive analysis with a quantitative percentage and qualitative approach.The results of the study showed that the people of Muara Merang Village had an average of 4.13 ha of land and the land they owned was burned an average of 1.53 ha. Overall, forest fires resulted in a decrease in community income with an average decrease of 20.56%. The highest decrease in income was experienced by the people in Pancuran Hamlet with an average decrease of 33.33%.The value of income decline for the Bakung Hamlet community was 11.35% and the lowest income decline was experienced by the Tebing Harapan Hamlet community with an average decline of 10.21%. The work constraints experienced by the community due to the fire were not tapping rubber, reduced working days, decreased sales value, not harvesting oil palm, reduced fish yields, difficulty in enriching oil palm or rubber plants, difficulty in cleaning up remaining branches after the fire, and reduced labor due to illness.